Functional state body students in scoliosis І–II phases - Ковальчук, В. Я. (Slobozhanskyi Herald of Science and Sport, 2011)
Students of special medical team diagnosed a satisfactory level of physical performance. Results Ruphye tests showed that the cardiovascular system in patients with scoliosis students working less efficiently and less adapted to physical stress than healthy. As a result pnevmotahography found that indicators of external respiration in scoliosis among students are significantly lower than in healthy peers, indicating the weakness of respiratory muscles, changes in the lung, displacement of the trachea and bronchi, change their size.